2005
DOI: 10.1128/mcb.25.9.3802-3813.2005
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Order in Which Nmd3p and Rpl10p Load onto Nascent 60S Ribosomal Subunits

Abstract: The large ribosomal subunit protein Rpl10p is required for subunit joining and 60S export in yeast. We have recently shown that Rpl10p as well as the cytoplasmic GTPase Lsg1p are required for releasing the 60S nuclear export adapter Nmd3p from subunits in the cytoplasm. Here, we more directly address the order of Nmd3p and Rpl10p recruitment to the subunit. We show that Nmd3p can bind subunits in the absence of Rpl10p. In addition, we examined the basis of the previously reported dominant negative growth pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(149 citation statements)
references
References 37 publications
(68 reference statements)
6
141
1
Order By: Relevance
“…RPL10 is a ubiquitous protein that participates in joining the 40S and 60S ribosomal subunits into a functional 80S ribosome; it organizes the union site to aminoacyl-tRNA; also, its incorporation into the 60S subunit is a prerequisite for the union of subunits and the initiation of translation (Eisinger et al, 1997;Loftus et al, 1997;West et al, 2005;Hofer et al, 2007). In addition, increasing evidence indicates that RPL10 protein from various organisms has multiple extraribosomal functions, besides being a constituent of the ribosome and participating in protein synthesis (Chan et al, 1996;Wool, 1996;Nika et al, 1997;Mills et al, 1999;Chávez-Ríos et al, 2003;Wen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RPL10 is a ubiquitous protein that participates in joining the 40S and 60S ribosomal subunits into a functional 80S ribosome; it organizes the union site to aminoacyl-tRNA; also, its incorporation into the 60S subunit is a prerequisite for the union of subunits and the initiation of translation (Eisinger et al, 1997;Loftus et al, 1997;West et al, 2005;Hofer et al, 2007). In addition, increasing evidence indicates that RPL10 protein from various organisms has multiple extraribosomal functions, besides being a constituent of the ribosome and participating in protein synthesis (Chan et al, 1996;Wool, 1996;Nika et al, 1997;Mills et al, 1999;Chávez-Ríos et al, 2003;Wen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, a mutation in Rpl10 demonstrated that it is essential for viability, as RPL10 organizes the union site to aminoacyl-tRNA; also, its incorporation into the 60S subunit is a prerequisite for the union of subunits and the initiation of translation (West et al, 2005;Hofer et al, 2007). Besides its role in translation, L10 has additional cellular roles.…”
mentioning
confidence: 99%
“…The latter is functionally linked to Nmd3 via the Xpo1/exportin export receptor pathway. 16,17 Studies in yeast show that in the cytoplasm, Rpl10 is necessary for joining the 60S and 40S subunits in a late step of translation initiation, 18 a functional reflection of its location at the interface between the two ribosomal subunits adjoining the A and P sites as well as the transpeptidyl transferase center. The high level of sequence conservation of RPL10 in all organisms and the location close to regulatory and catalytic sites of the ribosome indicate the importance of the structural and functional integrity of this protein in ribosome assembly and function, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their classic role of protecting from proteolysis, chaperones are also involved in adjusting the loading or transport processes. Yar1 directly interacts with Rps3 (S3) and acts as an anti-aggregation factor (35,37), and Sqt1 is a chaperone for Rpl10 (uL16) that facilitates loading of Rpl10 into 60S subunits (34,42). Rrb1 has direct interaction with Rpl3 (uL3), and overexpression of Rrb1 increased the level and nuclear accumulation of Rpl3 (36).…”
Section: Bcp1 Is a Chaperone Of Rpl23 And Required To Maintain Thementioning
confidence: 99%
“…It has been shown that karyopherins or chaperones interact with ribosomal proteins to maintain their solubility and also facilitate their loading into nascent ribosomal subunits (33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Figure 2 the Function Of Bcp1 Is Tightly Connected With Manmentioning
confidence: 99%